TOWARD A DIGITAL RELIGIOUS PEDAGOGY FOR GENERATION ALPHA: EXPLORING THE INTERSECTION OF ARTIFICIAL INTELLIGENCE, MOBILE LEARNING, AND RELIGIOUS MODERATION - Maulidatun Chaqoniya; Muhammad Makinnuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The changing landscape of education in the digital era has intensified the interaction between technology, learning processes, and character development. Within the context of Islamic Religious Education (IRE), the emergence of Artificial Intelligence (AI) and mobile learning has created new opportunities to enrich the learning experiences of Generation Alpha, a cohort that has grown up surrounded by digital technologies from an early age. At the same time, fostering religious moderation has become increasingly important as students are exposed to more complex and diverse information through digital environments. Although studies on AI, mobile learning, religious moderation, and Islamic education have expanded considerably, the connections among these areas remain fragmented and have yet to be integrated into a coherent conceptual framework. This review was developed through an examination of 25 articles selected from 76 publications retrieved from Scopus, Google Scholar, SINTA, and GARUDA databases. The selected literature was analyzed through thematic classification, comparative examination of findings, and conceptual synthesis to obtain a comprehensive understanding of current research developments. The results indicate that AI-related studies primarily focus on personalized learning, educational efficiency, and instructional innovation. Meanwhile, mobile learning is generally positioned as a means of expanding learning access, whereas religious moderation is predominantly discussed in relation to character development, tolerance, and inclusive values. The limited integration among these three domains highlights the need for the development of a digital religious pedagogy capable of connecting technological innovation with the cultivation of moderate character as a response to the educational needs of Generation Alpha in the future. ABSTRAK Perubahan lanskap pendidikan pada era digital menghadirkan perjumpaan yang semakin intens antara teknologi, proses pembelajaran, dan pembentukan karakter peserta didik. Dalam konteks Pendidikan Agama Islam (PAI), kemunculan Artificial Intelligence (AI) dan mobile learning membuka peluang baru untuk memperluas pengalaman belajar Generasi Alpha yang sejak awal kehidupannya telah berinteraksi dengan berbagai perangkat digital. Di sisi lain, kebutuhan untuk menanamkan nilai-nilai moderasi beragama menjadi semakin penting seiring meningkatnya kompleksitas informasi yang diakses peserta didik melalui ruang digital. Meskipun berbagai penelitian mengenai AI, mobile learning, moderasi beragama, dan pendidikan Islam terus berkembang, keterhubungan antarkajian tersebut masih belum tergambar secara utuh dalam satu kerangka konseptual. Kajian ini disusun melalui penelaahan terhadap 25 artikel yang dipilih dari 76 publikasi yang diperoleh melalui basis data Scopus, Google Scholar, SINTA, dan GARUDA. Literatur yang terpilih kemudian dianalisis melalui pengelompokan tema, perbandingan temuan, dan sintesis konseptual untuk memperoleh gambaran yang lebih komprehensif mengenai arah perkembangan penelitian. Hasil kajian memperlihatkan bahwa AI lebih banyak dibahas dalam kaitannya dengan personalisasi pembelajaran, efisiensi proses pendidikan, dan inovasi instruksional. Sementara itu, mobile learning cenderung diposisikan sebagai sarana peningkatan akses belajar, sedangkan moderasi beragama lebih sering dikaji dalam perspektif penguatan karakter, toleransi, dan nilai inklusivitas. Keterhubungan antara ketiga bidang tersebut masih relatif terbatas, sehingga diperlukan pengembangan pedagogi keagamaan digital yang mampu mempertemukan inovasi teknologi dengan pembentukan karakter moderat sebagai kebutuhan pendidikan Generasi Alpha pada masa mendatang.